Civil War and Uncivil Development Economic Globalisation and Political Violence in Colombia and Beyond - Maher, David (Rethinking Political Violence, 2018)
This book challenges the conventional wisdom that civil war inevitably stymies economic development and that 'civil war represents development in reverse'. While some civil wars may have adverse economic effects, Civil War and Uncivil Development posits that not all conflicts have negative economic consequences and, under certain conditions, civil war violence can bolster processes of economic development. Using Colombia as a case study, this book provides evidence that violence perpetrated by key actors of the conflict - the public armed forces and paramilitaries - has facilitated economic growth and processes of economic globalisation in Colombia (namely, international trade and foreign direct investment), with profoundly negative consequences for large swathes of civilians. The analysis also discusses the 'development in reverse' logic in the context of other conflicts across the globe. This book will be an invaluable resource for scholars, practitioners and students in the fields of security and development, civil war studies, peace studies, the political economy of conflict and international relations.